Literature Review: Pengaruh Gaya Kepemimpinan Dan Disiplin Kerja Terhadap Kinerja Karyawan - Nabillah Azzahra; Gusti Nurhayati; Aos Kuswandi (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Effective leadership style can build work discipline and productive employee performance, while ineffective leadership causes a decline in work discipline and employee performance. The method applied in this study is a literature review of 10 relevant scientific articles from 2015 to 2025. The findings of the analysis show that work discipline consistently has a positive and significant effect on employee performance. On the other hand, the impact of leadership style tends to vary; some studies show a significant effect, while others do not. However, simultaneously, the combination of leadership style and work discipline can increase employee motivation, sense of responsibility, and productivity. This study concludes that managing appropriate leadership style and improving work discipline are important strategies to optimize employee performance in an organization.